Islamic Leadership: Prophet Muhammad as a Role Model of Charismatic, Transformational and Servant Leader - Seno Santoso (CV. Syntax Corporation Indonesia, 2024)
The goal of this study is to investigate if a well-functioning business requires leaders who can effectively motivate and influence those around them. Many leadership models form the foundation for appointing leaders in many organizational domains. For a devoted Muslim, the Prophet Muhammad SAW serves as an ideal leader. The purpose of this qualitative research, conducted using qualitative methods, is to uncover the Prophet Muhammad SAW's leadership attributes in three leadership models: charismatic leadership, transformational leadership, and servant leadership. The results demonstrate how the Prophet Muhammad (PBUH) personified transformational leadership by presenting a visionary view of the future and encouraging his people to attain greatness. It also emphasizes his duty as a servant leader, emphasizing the needs of others, cultivating meaningful relationships, and instilling a sense of community inside the organization. By analyzing the principles implemented by the Prophet Muhammad (PBUH), this research provides valuable insight into the application of his leadership traits in contemporary leadership models, encouraging leaders to emulate the characteristics of his example for the betterment of their organizations and communities.